Diseño e implementación de un sistema de climatización para la sala de coordinaciones de la unidad académica de la Universidad Técnica de Cotopaxi - Almachi Chicaiza, Luis Alfredo (2016)
Nowadays in Ecuador health problems is reflected every day for workers who are perform their daily activities during a long workday, at the Technical University of Cotopaxi in the Academic Unit of Engineering Sciences and Applied, because of weather changes and temperature in Ecuador , It analyzes the area of the Coordinators room and identified the strategic points to place the diffusers and appropriate elements used to implement an air conditioning system in the teachers' room in order to control the temperature 21 °C of the place, this project has been obtained to maintain a constant temperature which had an adequate working environment, for each of the teachers who work in that place, the contribution of this project has provided labor benefits to students, teachers and interested people, being as, this project will help to develop future projects with similar features and for the development of new techniques to improve the service air conditioning and involving environmental conservation.